2010
DOI: 10.1038/gene.2010.3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of T-cell receptor-β alterations in the development of otosclerosis linked to OTSC2

Abstract: Otosclerosis is a common form of hearing loss, characterized by disordered bone remodeling in the otic capsule. Within the otosclerotic foci, several immunocompetent cells and immune-modulating factors can be found. Different etiological theories involving the immune system have been suggested. However, a genetic component is clearly present. In large otosclerosis families, seven autosomal-dominant loci have been found, but none of the disease-causing genes has been identified. This study focused on the explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
0
21
0
1
Order By: Relevance
“…Furthermore, another class of diseases in the network, myeloproliferative disorders, contains precancer and cancer, and includes polycythemia vera and chronic myelogenous leukemia, among others. The final constituent is otosclerosis, a disease causing hearing loss that has been found to be a T cell-mediated autoimmune disorder involving abnormal bone growth in the middle ear 29. Interestingly, both neuroblastoma and neoplasms of the testis are found in younger patients and most commonly involve germline mutations of specific genes that cause these phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, another class of diseases in the network, myeloproliferative disorders, contains precancer and cancer, and includes polycythemia vera and chronic myelogenous leukemia, among others. The final constituent is otosclerosis, a disease causing hearing loss that has been found to be a T cell-mediated autoimmune disorder involving abnormal bone growth in the middle ear 29. Interestingly, both neuroblastoma and neoplasms of the testis are found in younger patients and most commonly involve germline mutations of specific genes that cause these phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic investigations in large families segregating autosomal dominant otosclerosis identified seven loci ( OTSC1–5 , OTSC7 , OTSC8 ) (Tomek et al, 1998; Van Den Bogaert et al, 2001; Chen et al, 2002; Van Den Bogaert et al, 2004; Brownstein et al, 2006; Thys et al, 2007b; Bel Hadj Ali et al, 2008), but none of the corresponding genes has been found. However, a recent study suggests the implication of the T‐cell receptor β locus as the causative gene in the OTSC2 region (Schrauwen et al, 2010). Unlike the monogenic form of otosclerosis, sporadic cases without familial background are very common.…”
Section: Introductionmentioning
confidence: 99%
“…The human T cell receptor complex fulfills a prominent role in the immune system in the recognition of antigens and subsequent activation of T cells. By further functional exploration, we found a significantly lower TCRβ mRNA expression and lower circulating TCRαβ + T cells in blood from OTSC2 patients compared to controls and sporadic patients 45. Furthermore, we discovered additional significant disturbances in specific T cell subsets in these patients, including an increased CD28 null cell population, which are highly proinflammatory senescent T cells that have lost their CD28 expression.…”
Section: Linkage Studies For Otosclerosismentioning
confidence: 78%